Evaluation of land ecological security and driving factors in the Lower Yellow River Flood Plain based on quality, structure and function - Ge Zhai; Peng Ren; Ruihai Zhang; Bei Wang; Maoxin Zhang; Tingting He; Jinliang Zhang (Scientific Reports)
Abstract Land ecological security (LES) is crucial for human well-being and sustainable development, especially in areas like the Lower Yellow River Flood Plain (LYRFP), which faces flood threats, economic challenges, and ecological fragility. This study introduces a “Quality-Structure-Function” framework for evaluating LYRFP’s LES, incorporating ecological baselines and the impacts of land use changes on human well-being for a comprehensive assessment. Using the Optimal Parameter Geographic Detector (OPGD) model, we analyzed agricultural, industrial, and socio-economic factors as potential LES drivers. The findings indicate a gradual improvement in LES over the past two decades, with spatial variations—higher in upstream and estuarine areas and lower in the middle. Significant enhancements post-2010 were observed in Shandong Province, unlike the modest gains in Henan. Spatial heterogeneity in LES was evident across floodplain segments, with Jitai Beach witnessing the most decline, Dongying Beach the most improvement, and Zhengkai Beach the largest internal disparities. Economic growth and reduced agricultural activities positively impacted LES, while population growth-related human activities contributed to its decline. This study suggested land use safety improvements in LYRFP by considering spatiotemporal and influencing factors for regional ecological protection and development.